Climate Data Tools (CDT) and Automatic Weather Station Data Tool (ADT) Training for the Kenya Meteorological Department (KMD) - Faniriantsoa, Rija (2024)
The Automatic Weather Station Data Tool (ADT) is a web-based tool initially developed by the IRI in the context of Rwanda. The ADT helps to address challenges in accessing and processing Automatic Weather Station (AWS) data collected by different systems and networks such as Vaisala, Edkon, and KOICA, which are on different servers and in different formats, by enabling data quality control, processing, and visualization. In March 2022, the International Research Institute for Climate and Society (IRI) conducted a workshop to install ADT for the Kenya Meteorological Department (KMD) and provide training in its use. Upon KMD’s request, the IRI conducted a additional training on Climate Data Tool (CDT) and Automatic Weather Station Data Tool (ADT) at the Institute for Meteorological Training and Research (IMTR), Nairobi, from December 2 to December 13, 2024. The training was given to KMD and IMTR staff.